Pemberdayaan Perempuan Melalui Pelatihan Olahan Kakao: Sebuah Program Pengabdian Berbasis Komunitas - Yulindra Margaretha Numberi; Nurlita Dianingsih; Erlies P. Ramandey; Jeirel Wattilete; Raini Panjaitan; Chlia Riery G Skavanny; Mariza Ira Suabey (LPPM Uncen, 2025)
Local cocoa offers substantial value-addition opportunities for women-led microenterprises, yet gaps in processing skills, basic business practices, and market access constrain outcomes. This community service program empowered a women’s fellowship through structured, participatory training on cocoa-based product development. Objectives were to strengthen technical competencies for two ready-to-consume products (chocolate drink and chocolate jam), introduce basic business management (cash records, cost of goods sold/COGS, pricing), and build entry-level digital marketing and branding skills. Methods combined a community-based participatory approach (coordination, needs assessment, material preparation) with sequential sessions orientation, lecture discussion, hands-on practice, reflection and mixed-method evaluation (pre/post Likert survey and rubric-based observation). Ten participants completed the training. Results show participants replicated both products with more consistent quality, applied hygienic handling (heating/sterilization), and prepared simple business documents (cash ledger, COGS). Foundational brand assets (product name, basic label, initial promotional content) supported early commercialization, while collaborative work routines and peer champions emerged to sustain production. In conclusion, the intervention effectively enhanced technical, managerial, and promotional readiness and offers a practical model for community-based microenterprises that add value to local cocoa resources.